Desarrollo de habilidades socioemocionales y la intervención psicoeducativa en niños con autismo no verbal en nivel escolar - Campoverde Castillo, Kelly Mishel (2024)
The present research addresses the lack of socioemotional skills in children with non-verbal autism and its impact on social interaction, school adaptation and quality of life. Significant barriers are identified in the school environment, such as the scarcity of psychoeducational intervention programs and limited resources, which restrict the comprehensive development of these children. Through a qualitative approach, interviews with teachers and direct observations are analyzed to better understand students' behaviors, sensory responses, and cognitive and social skills. The results show that students with non-verbal autism require a highly personalized educational approach, with sensory and methodological adaptations to minimize stress and emotional crises. Students' reliance on the shadow teacher and sensory adaptations are crucial to avoiding meltdowns and promoting a controlled and safe learning environment. Additionally, the importance of collaboration between teachers and support professionals to create an inclusive environment is highlighted. It is concluded that innovative methodologies, such as ABA, TEACCH and AMMT, can be effective in the development of socio-emotional and functional skills. These interventions not only improve students' understanding and communication, but also address emotional regulation and crisis management. This project contributes to the scientific community by providing relevant data and a proposal of great importance that, when implemented, will promote school inclusion and improve the quality of life of students with non-verbal autism.